Natural rubber latex: Study of a novel carrier for Casearia sylvestris swartz delivery - Borges, Felipe Azevedo [UNESP]; Bolognesi, Luis Felipe Cesar [UNESP]; Trecco, Alberto [UNESP]; Drago, Bruno de Camargo [UNESP]; Arruda, Larisa Baldo de [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Pierri, Elaise Gonçalves [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP]; Santos, André Gonzaga dos [UNESP]; Miranda, Matheus Carlos Romeiro [UNESP]; Herculano, Rondinelli Donizetti [UNESP] (Hindawi, 2014)
Natural rubber latex (NRL) from Hevea brasiliensis has showed interesting biomedical properties as improving wound healing, cell adherence, tissue formation, and angiogenesis. It is used for biosynthesis of nanoparticles, sensors and prosthesis and for drug delivery systems (for drugs, plant extracts, and nanoparticles). To enhance its wound healing properties was incorporated Casearia sylvestris Swartz extract, whose pharmacological activity includes anti-inflammatory, analgesic, antiseptic, antiulcer, and antitumor due to its casearins and phenols. Results showed the prolonged release of its compounds (35 days) and the mechanism of release is super case II (𝑛 > 1) by Korsmeyer-Peppas model. Although SEM shows different sizes of clusters at the surface, the release is homogeneous through the biomembrane. FTIR shows no interaction between the matrix and the extract, with computation of the presence of some casearins.
Keywords: Casearia sylvestris Swartz; Latex membrane; biomaterials